Diet Supplementation Influences Ghrelin System Expression in the Skin Appendages of the Sheep - Margherita Maranesi; Cecilia Dall’Aglio; Sara Moscatelli; Elisa Palmioli; Paola Coliolo; Daniele Marini; Gabriella Guelfi; Paola Scocco; Francesca Mercati (Veterinary Sciences)
Ghrelin (GhRL) is an orexigenic hormone influenced by nutritional state. It plays a role in skin repair and diseases, though little information exists regarding its function in this organ. GhRL and its receptor were investigated in the skin of sheep under different feeding conditions to explore GhRL system presence and possible modifications due to diet. Three-year-old female sheep were free to graze from June to the pasture maximum flowering (MxF group) and from this period to maximum dryness addicted (Exp group) or not (MxD group) with 600 gr/die/head of barley and corn. Skin samples were processed for immunohistochemistry and real-time PCR. The immunostaining showed the presence of the GhRL system in skin appendages. Indeed, the ligand was localized in the hair follicles whereas the receptor was also observed in sweat glands and smooth muscle cells. The expression of both genes was significantly higher in the Exp group (3.6 and 2.9 folds respectively, p < 0.05) compared with the MxF group. These results suggest that the GhRL system is involved in the regulation of hair follicles and sweat glands. In addition, diet supplementation may positively modulate the expression of GhRL and its receptor in the skin.